Documenting of extravasation of cytotoxic agents - Savić Maja; Stanisavljević Sanja; Tadić Dušanka (Association of Nurses Technicians and Midwives, 2020)
As a potential complication of a systemic administration of cytotoxic agents, extravasation requires particular caution of all health practitioners involved in treatments of oncological patients. In the light of the fact that more than 100.000 doses of chemotherapy are indicated worldwide and more than 1.000.000 intravenous infusion of cytostatic drugs are administered on daily bases, it is upsetting that in the case of cytostatic administration through peripheral intravenous cannulas extravasation occurs in 0,5 to 6% of oncological patients, while in the case of administration through central venous lines it occurs in 6% of the cases. Each extravasation results in tissue damage and depending on type and features of the administered substance can be manifested in different forms, from skin reaction to tissue necrosis. By highlighting the multiple significance of documenting and accident reporting, the authors state the necessary elements and propose the form of a nurse documenting list for the cases of extravasation of cytostatic agents. A nurse must document the following data on an accident: patient's name and surname, date of birth, name of the clinics, primary oncological diagnosis, date and time of extravasation, name of the cytotoxic drug, symptoms and signs of extravasation and the measures undertaken. The accurate documenting and reporting of accidents are legally binding for health practitioners, particularly nurses, as a result of the need to map the risk factors of their occurrence, to assess compliance of the standard nursing procedures in administration of cytostatic therapy, to follow up the course of the management of complications, outcomes and the undertaken measures but also to improve the existing and develop new preventive strategies.